“May Their Limbs Melt, Just as This Lead Shall Melt...”: Sympathetic Magic and Similia Similibus Formulae in Greek and Latin Curse Tablets (Part 1) - Franek, Juraj; Urbanová, Daniela (Philologia Classica, 2019)
In this contribution, we present a representative corpus of similia similibus formulae attested in ancient Greek and Latin curse tablets or defixiones. The simile formulae, attested in about 80 tablets in widely differing states of preservation and legibility, are introduced in the context of sympathetic magic and, in contradistinction to literary similes, as performative utterances that are based on a persuasive analogy. This analogy operates in the general form of “just as X possesses property P, so let also Y possess property P”, in which Y is the target or victim of the curse, while X and P are variables that change in accordance with the intended results. We provide a provisional taxonomy of simile formulae, offer new readings and interpretations of some defixiones, and compare Greek and Latin documents. Due to its length, the paper has been divided into two parts. In the first part, presented here, we focus on comparata that reference the materiality of the tablet itself and comparata referencing corpses or ghosts of the dead. The remaining comparata, namely animals, historiolae and rituals, aversus formulae and unusual orientations of the script, “names”, and drawings, will be presented in a follow-up paper, to be published in the next issue of Philologia Classica.